Commonly used nasal packs after septal surgery: A comparative study - ., BABAR HUSSAIN KHAN (Journal of Fatima Jinnah Medical University, 2018)
Objective: To compare fingerstall, vaseline gauze pack, and BIPP pack after septoplasty under local anaesthesia, in terms of ease of insertion, removal, haemostatic effect and cost effectiveness. Study Design: Prospective comparative study. Place and Duration of Study: Department of ENT, Combined Military Hospital Lahore. March 2007 to December 2009. Patients and Methods: Seventy five patients undergoing septoplasty were enrolled into this randomized, prospective trial, with ages ranging from 17 to 32 years (mode= 18, median=24, mean= 21) with male to female ratio of 5:1. The patients were divided into three equal groups by simple random sampling. All the patients underwent septoplasty for deviated nasal septum under local anaesthesia. Group A was packed with glove fingerstall and group B with rolled vaseline gauze and group C with ribbon gauze impregnated with bismuth iodoform paraffin paste (BIPP). All procedures were performed by the same surgeon to standardize the procedure and results. The packs were removed after 24 hours of surgery. Packs were assessed in terms of pain on insertion, control of bleeding, ease of removal and cost effectiveness. Statistical analysis was done using SPSS version 16 and P value < 0.05 was considered significant. Results: In Group A, 4 (16%) and in group B, 5 (20%) and in group C, 9 (36%) had moderate to severe pain on pack insertion.Four patients (16%) in group A, 02 (8%) in group B, and 02 (8%) patients in group C, had profuse and/ or persistent bleeding requiring repacking with the same pack. Four patients (16%) In Group A and 6 (24%) in group B, and 11 (44%) in group C, had moderate to severe pain on pack removal. Conclusion: There was no significant difference in the three types of packs with regards to pain on insertion, haemostatic effect and ease of removal. (p>0.05). Fingerstall and Vaseline gauze pack were more cost effective as compared to BIPP pack (p <0.05).